Relationship between admission Q waves and microvascular injury in patients with ST-elevation myocardial infarction treated with primary percutaneous coronary intervention. (15th December 2019) - Tiller, Christina; Reindl, Martin; Holzknecht, Magdalena; Innerhofer, Lukas; Wagner, Miriam; Lechner, Ivan; Mayr, Agnes; Klug, Gert; Bauer, Axel; Metzler, Bernhard; Reinstadler, Sebastian Johannes
Abstract: Background: Using comprehensive cardiac magnetic resonance (CMR) imaging in patients suffering from ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI), we sought to investigate the association of admission Q waves with microvascular injury (microvascular obstruction (MVO) and intramyocardial haemorrhage (IMH)). Methods: This prospective observational study included 195 STEMI patients treated with pPCI. Admission 12-lead electrocardiography was evaluated for the presence of pathological Q waves, defined as a Q wave duration of >30 ms and a depth of >0.1 mV. CMR was performed at 3 (interquartile range: 2–5) days after pPCI to determine infarct characteristics including MVO (late gadolinium enhancement) and IMH (T2* mapping). Results: Admission Q waves were observed in 53% of patients (n = 104). These patients had a significantly lower BMI (p = 0.005), more frequent left anterior descending artery as culprit lesion (p = 0.005), were less frequent smokers (p = 0.048) and had higher rates of pre-interventional TIMI flow 0 (p = 0.018). Patients with Q waves showed a significantly larger infarct size (19%vs.12% of left ventricular mass, p < 0.001), lower ejection fraction (49%vs.54%, p = 0.001), worse global strain parameters (all p < 0.005) and more severe microvascular injury (MVO: 68%vs.34%, p < 0.001; IMH: 40%vs.20%, p = 0.002). Q waves remained associated with both MVO (odds ratio: 5.23, 95% confidence interval: 2.58 to 10.58, p < 0.001) and IMH (odds ratio: 3.94, 95% confidence interval: 1.83 to 8.46, p < 0.001) after adjusting for potential confounders (culprit lesion, pre-interventional TIMI flow 0, total ischemia time, ST-segment elevation). Conclusions: Admission Q waves, derived from the readily available ECG, emerged as independent early markers of CMR-determined microvascular injury in STEMI patients undergoing pPCI. Highlights: Admission Q waves showed significant association with MVO and IMH. Admission Q waves revealed independent prediction of MVI. Patients presenting with admission Q waves are related to adverse clinical outcome.